The effect analysis of earning management and family control on the Z-score model of financial distress prediction - Haji-Seseang, Rahmawati; Habbe, Abdul Hamid; Rasyid, Syarifuddin; Nirwana, Nirwana (Business: Theory and Practice, 2023)
The validity of the use of financial statements as a source of information for detecting financial distress is questionable because of the opportunistic behaviour of the company’s management. This study aims to analyse the effect of accrual earnings management, real earnings management, and family control on the Z-score financial distress prediction. Using the sample that includes 372 firm years of observations for the 2017 to 2019 periods listed on the Indonesia Stock Exchange, this study found that accrual earnings management, real earnings management, and family control variables affect the Z-score financial distress prediction and cause a higher probability for the company to be in the category of better financial condition. The novelty of this study lies in earnings management and family control as factors that affect the category of assessment and the probability of assessing the company’s financial condition as a better company. Empirical evidence from this study is important for investors and company creditors, as input to consider these factors in using the company’s financial distress prediction model. For standard setters, the results of this study can be used as input for establishing corporate governance design rules to improve the quality of financial information.